Copper Metallogel as Potential Drug Carrier for Anti‐Inflammatory Drugs. Issue 34 (9th September 2021) - Choudhary, Priyanka; Gaur, Ruchi; Rambabu, Darsi; Dhir, Abhimanew; Gupta, Ankush; Pooja,
Abstract: Copper based Metal‐Organic Gels (MOGs) were evaluated for their efficiency as drug carrier for four anti‐inflammatory drugs viz . 5‐Fluorouracil (5FU), Phenidone (PN), Ibuprofen (IBP) and Cisplatin (CP). Copper(II)‐benzene tricarboxylic acid (CuBTC) was used as a precursor for the loading and releasing of these drugs. The distinctive porous nature of the gel provided the high loading efficiency for these anti‐inflammatory drugs. Among all the drugs evaluated, CuBTC@5FU exhibited maximum drug loading (88.1 %) and releasing (95 %) efficiency at physiological pH 5.2, which was attributed to the strong hydrogen bonding interactions between CuBTC and fluoride of 5FU. Abstract : Copper based metal‐organic gels (MOGs) are well proficient carrier for four anti‐inflammatory drugs, 5‐Fluorouracil (5FU), Phenidone (PN), Ibuprofen (IBP), Cisplatin (CP) delivery at physiological pH 5.2 and 7.2.